Study of polymer-stabilized cholesteric liquid crystals for reflective displays in active matrix driving - Kuan-Wu Lin; Jhih-Yi Lu; Heng-Yi Tseng; Chien-Yi Lin; Liang Ying Huang; Yi-Ling Lin; Huan-Hsuan Chang; Tsung-Hsien Lin (Journal of Information Display)
This paper attempts to explore the feasibility of using cholesteric liquid crystals (CLCs) for reflective displays in active matrix (AM) driving. The study focuses on reverse mode polymer-stabilized cholesteric liquid crystals (PSCLCs) to overcome the inherent bistability of CLCs and achieve faster response times for switching between bright and dark states. Key parameters such as cell gap, monomer concentration, polymerization temperature, and different monomer types and liquid crystal hosts are systematically investigated to optimize the electro-optical properties of the liquid crystals for active matrix driving. The research demonstrates that PSCLCs can operate within a 15 V driving voltage range while maintaining a good bright-dark state contrast ratio (>10) and a response time of less than 42 ms. This suggests significant potential for their application in dynamic reflective display technologies.